MAINTAINING TRADITIONAL CULTURAL COMMUNICATION IN DIGITAL MEDIA (STUDY ON THE MAINTENANCE OF THE SORONG SERAH AJI KRAMA TRADITION ON COMMUNITY SOCIAL INTERACTION IN BAYAN, NORTH LOMBOK) - Asmarani Pamela Paganini; I Nyoman Murba Widana; Made Sumari; I Ketut Putu Suardana (Universitas Gunadarma, 2023)
Sorong serah aji krama tradition is one of the wedding ceremonies series by the Sasak tribe that has been preserved to this day. This tradition is a form of traditional cultural expression of society represented through symbols on the means used that can influence the social interaction of the societies in Bayan in daily life, given that the symbols in the tradition are closely linked with how humans should act in society. Therefore, the issue discussed in this research is: (1) how does the process of sorong serah aji krama tradition in Bayan. (2) how is the symbolic interaction in the sorong serah aji krama tradition in Bayan? (3) What are the implications of symbolic interaction in the Sorong serah tradition over the social interaction of the societies in Bayan? This research object is a tradition of solid serah aji krama in Bayan, north Lombok, that will be researched using qualitative descriptive methods through observations, interviews, and documentation techniques of data collection. This research tries to find the symbolic form of interaction and the implication of symbolic interaction to the social interaction of society by using the symbolic interaction theory. The conclusion is this tradition begins with memulang, sejati selabar, tekang pengeraos, sorong serah aji krama, and ends with tekang pengeraos. Symbols that appear consist of gegawan, language, and behavior. The whole aspect of the symbol in the traditions relating to the godhead, nature, and social relations implicates the social interaction of indigenous societies.